2011
DOI: 10.1007/s00468-011-0650-y
|View full text |Cite
|
Sign up to set email alerts
|

Why don’t branches snap? The mechanics of bending failure in three temperate angiosperm trees

Abstract: Living tree branches are almost impossible to snap. Some show ''greenstick fracture'', breaking halfway across before splitting along their length, while others simply buckle. In this study we investigated the bending failure of coppice branches of three temperate angiosperm trees: ash, Fraxinus excelsior; hazel, Corylus avellana; and white willow, Salix alba. We carried out bending tests, and made a series of observations on the structure, density and tensile and compressive strength of their wood to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…We have shown that these branches are significantly smaller, weaker, and more flexible than those used in the main structure of the nest. Compliant living branches hardly ever break completely across (13,14), and to detach them takes a degree of skill. Observations of nests revealed that the broken ends of detached branches often had a tail of bark or wood material (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have shown that these branches are significantly smaller, weaker, and more flexible than those used in the main structure of the nest. Compliant living branches hardly ever break completely across (13,14), and to detach them takes a degree of skill. Observations of nests revealed that the broken ends of detached branches often had a tail of bark or wood material (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3A), breaking branches only halfway across and not detaching them. Greenstick fracture is the natural fracture mode expected from the denser wood types typical of canopy tree species (13,14) and by a considerable margin was the most prevalent fracture type recorded within the nest structures. It could be argued that the predominance of greenstick fracture within the nest structures is because orangutans are not able to completely break and detach the larger, stronger branches used in the structural base of the nest.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations